2013
DOI: 10.1039/c2md20212c
|View full text |Cite
|
Sign up to set email alerts
|

Mapping histamine H4receptor–ligand binding modes

Abstract: Computational prediction of ligand binding modes in G protein-coupled receptors (GPCRs) remains a challenging task. Systematic consideration of different protein modelling templates, ligand binding poses, and ligand protonation states in extensive molecular dynamics (MD) simulation studies enabled the prediction of ligand-specific mutation effects in the histamine H4 receptor, a key player in inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 72 publications
0
54
1
Order By: Relevance
“…In a study of Schultes et al the binding mode of substituted and unsubstituted indolecarboxamides and 2-aminopyrimidines were reported [47]. They built separate H4R homology models using H1R or the β2-adrenergic structures.…”
Section: H4 Receptormentioning
confidence: 99%
“…In a study of Schultes et al the binding mode of substituted and unsubstituted indolecarboxamides and 2-aminopyrimidines were reported [47]. They built separate H4R homology models using H1R or the β2-adrenergic structures.…”
Section: H4 Receptormentioning
confidence: 99%
“…This result indicated that celecoxib is a potent ligand for ERα [1,3,17,19,21]. In vitro tests to confirm these in silico results were therefore required [17,19,[29][30][31][32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 92%
“…On the other hand, in silico approaches could assist in the explanation of in vitro tests [35,[40][41][42][43][44][45][46][47]. Very recently, the virtual screening protocol mainly referred in this study [17,19] was retrospectively re-validated [20] using the newest benchmarking dataset provided by Mysinger et al [36].…”
Section: Resultsmentioning
confidence: 99%
“…A recent example on the mapping of protein–ligand binding in H4R has conclusively established that this is feasible [69]. Homology models from various templates have been built, and a combination of docking and molecular dynamics (MD) has been employed.…”
Section: G-protein-coupled Receptorsmentioning
confidence: 99%